Pancreatic Kininogenase Ameliorates Renal Fibrosis in Streptozotocin Induced-Diabetic Nephropathy Rat - Dan Zhu; Linlin Zhang; Lijuan Cheng; Liansheng Ren; Jie Tang; Dianjun Sun (Karger Publishers, 2016)
Background/Aims: We aimed to evaluate whether pancreatic kininogenase (PKase) can relieve renal fibrosis and investigate its mechanisms in diabetic nephropathy (DN) rats Methods: We established streptozotocin (STZ) induced-DN rats. After treatment with PKase for 4 weeks, urinary weight, urinary protein content and blood glucose concentration were detected, and then renal histopathological changes were examined using Hematoxylin and Eosin (H&E) and Masson's thrchrome staining. In addition, the expressions of miR-433, transforming growth factor-β1 (TGF-β1) and antizyme inhibitor 1 (Azin1) were detected by qRT-PCR and/or western blotting. Results: PKase reduced urinary weight, urinary protein contents and blood glucose concentrations. PKase treated DN rats exhibited less renal fibrosis than untreated DN rats (P P P Conclusions: PKase might not only inhibit the development of DN by reducing urinary weight, urinary protein content and blood glucose concentration in DN rats, but also relieve renal fibrosis in DN rats through inhibiting the expression of TGF-β1, and miR-433 and Azin1 might involve in this process.